2012
DOI: 10.1111/j.1365-3156.2012.03068.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening of patients with tuberculosis for diabetes mellitus in China

Abstract: Abstractobjective There is a high burden of both diabetes (DM) and tuberculosis (TB) in China, and this study aimed to assess feasibility and results of screening patients with TB for DM within the routine healthcare setting of six health facilities.method Agreement on how to screen, monitor and record was reached in May 2011 at a stakeholders' meeting, and training was carried out for staff in the six facilities in July 2011. Implementation started in September 2011, and we report on 7 months of activities up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
80
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 17 publications
16
80
4
Order By: Relevance
“…8 A recent report from China suggested that the incorporation of DM results into TB-DM registers that are linked to TB registers, combined with formal quarterly reports on numbers of patients screened for DM and numbers diagnosed with DM and referred for care, works well, and this could be a template for other countries to follow. 9 In conclusion, this study shows that the routine practice of screening TB patients for DM in Fiji is suboptimal and needs to improve. A fi rst important step will be a policy decision about i ncorporating screening results into TB registers and including the subsequent DM data in the quarterly reports, i.e., 'what gets measured gets done'.…”
Section: Discussionmentioning
confidence: 99%
“…8 A recent report from China suggested that the incorporation of DM results into TB-DM registers that are linked to TB registers, combined with formal quarterly reports on numbers of patients screened for DM and numbers diagnosed with DM and referred for care, works well, and this could be a template for other countries to follow. 9 In conclusion, this study shows that the routine practice of screening TB patients for DM in Fiji is suboptimal and needs to improve. A fi rst important step will be a policy decision about i ncorporating screening results into TB registers and including the subsequent DM data in the quarterly reports, i.e., 'what gets measured gets done'.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid false-positive results, determining multiple parameters correlated to chronic hyperglycemia is especially important in TB patients, as active TB can result in transient hyperglycemia. 7 Such a test would be useful not only for screening but also for glycemic control monitoring in patients already identifi ed as having prediabetes or DM.…”
Section: Target Product Profile For a Diabetes Point-of-care Screeninmentioning
confidence: 99%
“…4 Although the links between diabetes and TB have been known for decades, 5,6 the unprecedented global rise in DM led the World Health Organization (WHO) and the International Union Against Tuberculosis and Lung Disease to issue a global recommendation in 2011 that all TB patients should be screened for DM and vice versa, 4 and countries including China and India have commenced TB-DM screening programs. [7][8][9] Despite this, global response to the crisis has been hampered by a lack of knowledge regarding the most appropriate screening methods and technologies to use in TB settings. 4 The need to develop and evaluate more accu-rate, rapid, non-invasive and cost-effective point-ofcare (POC) diagnostic and monitoring tests-including measurements of blood glucose and blood glycated hemoglobin (A1c)-was acknowledged in 2011 at a consultation meeting of global experts on TB and DM.…”
mentioning
confidence: 99%
“…Conclusively, this study proved to be advantageous as it shows that screening active TB in diabetic clinics leads to early detection of TB, prompt treatment and better clinical outcome for anti-TB treatment as well as routine DM care. Additionally, it also sets an example for establishing strong monitoring, recording and reporting of TB-DM cases 50 . Screening in India resulted in the case rate of TB among diabetics to be higher than TB case notification released by Regional National Tuberculosis Control Programme (RNTCP), i.e.…”
Section: Screening and Diagnosismentioning
confidence: 99%
“…This was inspired by a study conducted in China 50 . In 2011, a prospective observational study was done in China to monitor the implementation project for screening in five diabetic clinics for TB, strictly based upon the criteria set by China National TB Control Programme (NTP).…”
Section: Screening and Diagnosismentioning
confidence: 99%